Disentangling the Relationship Between Social Ties, Prison Visitation, and Recidivism - Atkin-Plunk, Cassandra A. (Criminal justice and behavior, 2018)
Studies find inmates who receive visits while incarcerated are less likely to recidivate upon release, especially when visits are from spouses and occur frequently throughout incarceration. Absent from these studies is measurement of the quality of an inmate’s relationships prior to incarceration, which may play a more significant role in criminal desistance than visitation itself. Longitudinal data from 205 incarcerated male and female adult offenders were used to test the mediating effects of visitation for offenders with varying levels of preincarceration relationships on recidivism. Findings indicate that quality of an inmate’s preincarceration relationships is more important in reducing the odds of recidivism than visitation. When quality of relationships was taken into account, visitation became nonsignificant in predicting the odds of recidivism. Most critical, a strong maternal relationship prior to incarceration was associated with a reduction in recidivism subsequent to a period of incarceration.